Effects of high concentrations of crude glycerin in diets for feedlot lambs: feeding behaviour, growth performance, carcass and non-carcass traits - Costa Almeida, Marco Tulio [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; Paschoaloto, Josimari Regina [UNESP]; Perez, Henrique Leal [UNESP]; Carvalho, Vanessa Barbosa de [UNESP]; Castro Filho, Edivilson Silva [UNESP]; Castello Branco van Cleef, Eric Haydt [UNESP] (Csiro Publishing, 2018)
The effects of high concentrations of crude glycerin were investigated in diets for feedlot lambs. Forty crossbred (Santa Ines x Dorper) uncastrated male lambs (21.7 +/- 2.7 kg bodyweight) were assigned to a complete randomised block and subjected to four experimental diets containing 0, 100, 200, or 300 g crude glycerin/kg DM. Animals were weighed at 14-day intervals and were harvested when they reached similar to 35 kg bodyweight. The feed intake, feeding behaviour, growth performance, carcass and meat traits, and edible non-carcass components were evaluated. The inclusion of more than 100 g/kg crude glycerin in the diets increased days on feed and decreased DM intake and average daily gain. Crude glycerin increased number of chews and the time spent chewing per feed bolus. There were no effects of crude glycerin on pH and colour of Longissimus muscle at 45 min or 24 h after slaughter, as well as on other carcass and edible non-carcass characteristics. The addition of crude glycerin reduced perirenal fat without detrimental effect on others fat deposition sites. In conclusion, the addition of up to 100 g/kg DM in diets for crossbred finishing lambs seems to be the most interesting strategy, as it promotes greatest animal performance. However, the inclusion of up to 300 g/kg DM of the by-product could be possible depending on glycerin market price and the structure of feedlot operation, with favourable economic results despite high inclusions reflect in greater number of days on feed.
Keywords: by-product; glycerol; sheep